2010
DOI: 10.1111/j.1399-3038.2010.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of atopic dermatitis in children is influenced by their parents’ education: results of two cross-sectional studies conducted in Upper Austria

Abstract: Atopic dermatitis (AD) is an important health problem worldwide. Several studies have shown that a positive family history is a strong risk factor. We studied the prevalence of AD among 23,583 Austrian school children and examined the association between the prevalence of AD in children and their parents' education at two points in time. As part of the International Study of Asthma and Allergy in Childhood programme, two cross-sectional studies were conducted in Upper Austria (Federal State of Austria) between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 53 publications
3
19
0
4
Order By: Relevance
“…Prevalence data on trends in atopic eczema for western Europe are shown in Table 9 [24], [55][63]. Parental- and self-report of atopic eczema symptoms were reported in five countries [55], [56], [59], [60], [62], [63].…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence data on trends in atopic eczema for western Europe are shown in Table 9 [24], [55][63]. Parental- and self-report of atopic eczema symptoms were reported in five countries [55], [56], [59], [60], [62], [63].…”
Section: Resultsmentioning
confidence: 99%
“…126 A higher level of parental education is a risk factor for disease, but the effect of socioeconomic status is unclear. 126, 127 Previous studies found a higher risk of AD in higher socioeconomic groups, but more recent studies failed to confirm these findings. 128, 129 Living in urban areas appears likely to increase the risk of atopic dermatitis, but studies attempting to identify causative environmental agents have not been conclusive.…”
Section: Risk Factors For Disease Developmentmentioning
confidence: 99%
“…Notably, China had the lowest prevalence in the world. The reasons for these differences in AD prevalence are poorly understood, but industrialization and socioeconomic factors have been implicated [5,6,7,8,9,10]. …”
Section: Prevalence Of Admentioning
confidence: 99%